2015
DOI: 10.1002/jssc.201401095
|View full text |Cite
|
Sign up to set email alerts
|

Liquid chromatography with diode array detection combined with spectral deconvolution for the analysis of some diterpene esters in Arabica coffee brew

Abstract: 14In this manuscript, the separation of four kahweol esters and four cafestol esters that are present in 15Arabica coffee brews was investigated using HPLC/DAD. Those compounds could not be baseline 16 separated in a single chromatogram using RP-LC but the kahweol esters could be selectively detected by 17 setting the wavelength at 290 nm. In this case the four kahweol esters were baseline separated allowing 18 for their quantification. Such approach was not possible for the cafestol esters and spectral deconv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 43 publications
0
19
1
Order By: Relevance
“…Another study from the UP by Erny, Moeenfard and Alves (2015) showed that most studies on the subject were performed after saponification of kahweol and cafestol esters. But to better understand the composition of the diterpene esters in boiled Arabica coffee drinks, the authors performed the quantification by HPLC-DAD combined with spectral deconvolution, since the kahweol and cafestol esters eluted together.…”
Section: The Diterpene Content Of Different Coffee Beveragesmentioning
confidence: 99%
“…Another study from the UP by Erny, Moeenfard and Alves (2015) showed that most studies on the subject were performed after saponification of kahweol and cafestol esters. But to better understand the composition of the diterpene esters in boiled Arabica coffee drinks, the authors performed the quantification by HPLC-DAD combined with spectral deconvolution, since the kahweol and cafestol esters eluted together.…”
Section: The Diterpene Content Of Different Coffee Beveragesmentioning
confidence: 99%
“…Prior to the analysis, the diterpenes were extracted from coffee beans using organic solvents, such as n-hexane, diethyl ether, petroleum ether, followed by saponification by an alcoholic KOH solution. Diterpene compounds were also determined in Arabica coffee by HPLC-DAD (Erny, Moeenfard & Alves, 2015). In Arabica and Robusta coffee beverages, previously unknown compounds affecting their flavor were identified by high resolution HPLC-MS (Nascimento et al, 2015).…”
Section: Determination Of Diterpenes (Kahweol and Cafestol) In Coffeementioning
confidence: 99%
“…Those files were opened using Matlab R2013b and the chromatographic data loaded into a two-dimensional (2D) array. The Matlab function was programmed using Matlab R2013b and can be found in previous published study (Erny et al 2015). Through applying spectral deconvolution to every spectrum, deconvoluted chromatograms were obtained that are specific to the cafestol and kahweol esters.…”
Section: Deconvolutionmentioning
confidence: 99%
“…Free diterpenes (either originally present or after cleavage of the esters) can be analyzed using liquid or gas chromatography (Erny et al 2015) as well as spectrophotometric method (Dias et al 2013). However, to provide information on individual esters, diterpene esters should be analyzed through HPLC only after gel permeation chromatography or solid phase extraction (Kurzrock and Speer 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation